Space Allocation of RAPs Zoning Plan in Pasaman Barat Regency Based on the Minister Regulation of Marine and Fisheries No. 31/PERMEN-KP/2020 - Arlius Arlius; Suparno Suparno; Erni Husni (Pascasarjana, Universitas Negeri Padang, 2022)
Regional Aquatic Protected Areas (RAPs) of Pasaman Barat Regency is a protected and managed water area covering the waters of Pangka Island, Pigago Island, and Taluo Island. The purpose of the study was to analyze the zoning plan for the Marine Protected Area (MAPs) and analyze the activities that may or may not be carried out in the RAPs in Pasaman Barat Regency. The research method used is the survey method. The results of the analysis of the zoning plan for the conservation area of ​​Pasaman Barat Regency have 6,122.14 Ha, consisting of a core zone of 157.93 Ha, a limited use zone of 5,927.09, and other zones/port zones of 37.12 Ha. All activities are not allowed in the core zone except educational activities (permitted with conditions). Limited use zones for economic activities include small-scale fishing and small fisherman shipping (permitted), regular domestic passenger ship shipping (permitted), and fishing vessel traffic > 10 GT (permitted). Activities for the social and economic community in the limited use zone are allowed with conditions. Other zones/port zones are used for port activities to support tourism. The Pasaman Barat Regency MPA zoning plan is an important document for the West Sumatra Provincial Government as the basis for granting a water business permit in a conservation area.